The ‘Care’ in Caregiving The Multiple Sclerosis experience for the healthy family members (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
The present study seeks to analyze the meaning of experience lived by the relatives of a Multiple Sclerosis patient. The methodology employed is hermeneutical phenomenology based on the philosophy of Heidegger. The disease appeared to be experienced as an entity. The experience caused changes in family cohesion as well as at the level of empathy about the meaning of health
Keywords: Multiple Sclerosis; family; caregiver; hermeneutical phenomenology; Heidegger